2018
DOI: 10.1038/s42003-018-0109-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating glucose levels inversely correlate with Drosophila larval feeding through insulin signaling and SLC5A11

Abstract: In mammals, blood glucose levels likely play a role in appetite regulation yet the mechanisms underlying this phenomenon remain opaque. Mechanisms can often be explored from Drosophila genetic approaches. To determine if circulating sugars might be involved in Drosophila feeding behaviors, we scored hemolymph glucose and trehalose, and food ingestion in larvae subjected to various diets, genetic mutations, or RNAi. We found that larvae with glucose elevations, hyperglycemia, have an aversion to feeding; howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 72 publications
1
23
0
Order By: Relevance
“…While Dilp1, Dilp2, Dilp3 and Dilp5 are all produced by the IPCs, previous studies have uncovered significant differences in regulation, secretion, and phenotypic effects of these IPC-derived Dilps (Brogiolo et al, 2001;Zhang et al, 2009;Okamoto et al, 2009;Grönke et al, 2010;Cognigni et al, 2011;Stafford et al, 2012;Bai et al, 2012;Linneweber et al, 2014;Cong et al, 2015;Liu et al, 2016;Nässel & Vanden Broeck, 2016;Post et al, 2018Post et al, , 2019Semaniuk et al, 2018;Ugrankar et al, 2018;Brown et al, 2020). We therefore wanted to determine the individual contributions of IPC-derived Dilps to body size in each sex.…”
Section: Loss Of Individual Dilp Genes Causes a Female-specific Decrementioning
confidence: 99%
“…While Dilp1, Dilp2, Dilp3 and Dilp5 are all produced by the IPCs, previous studies have uncovered significant differences in regulation, secretion, and phenotypic effects of these IPC-derived Dilps (Brogiolo et al, 2001;Zhang et al, 2009;Okamoto et al, 2009;Grönke et al, 2010;Cognigni et al, 2011;Stafford et al, 2012;Bai et al, 2012;Linneweber et al, 2014;Cong et al, 2015;Liu et al, 2016;Nässel & Vanden Broeck, 2016;Post et al, 2018Post et al, , 2019Semaniuk et al, 2018;Ugrankar et al, 2018;Brown et al, 2020). We therefore wanted to determine the individual contributions of IPC-derived Dilps to body size in each sex.…”
Section: Loss Of Individual Dilp Genes Causes a Female-specific Decrementioning
confidence: 99%
“…In the literature, changes of insulin level and insulin signaling in AD brains are still debated and inconsistent 26 . By using RT-PCR analyses, we found that the head level of thor ( 4EBP homolog in the fly ) , which is reduced by insulin 27 , was decreased in Aβ flies (Fig. 3a); the level of head tobi (target of brain insulin) was increased in Aβ flies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Sugar consumption is regulated depending on the satiation state of the animal. In Drosophila larvae, hemolymph carbohydrate levels negatively correlate with sucrose consumption [27].…”
Section: Sucrose Consumption Specifically Suppresses Larmmentioning
confidence: 99%